Structure and Cenozoic evolution of Western Cuba fold and thrust belt - Saura, E.; Vergés, J.; Brown, D.; Lukito, P.; Soriano, S.; Torrescusa, S.; García, R.; Sánchez, J. R.; Sosa, C.; Tenreyro, R. (TRABAJOS DE GEOLOGÍA, 2010)
We present balanced and restored cross-sections across the Western Cuba fold and thrust belt,based on MCS profiles, field data and balancing techniques. The cross-section intersects the Los PalaciosBasin, the Sierra del Rosario antiformal stack, the Bahía Honda unit, the frontal imbricated thrustsheets, the foredeep basin and a buried, geometrically inferred duplex. The minimum calculated shorteningis 130 km. Syntectonic deposits and a forward kinematic model provide a good constraint for theCenozoic tectonic evolution of the orogen, from the emplacement of the Bahía Honda unit to the finalinfill of the foredeep.